Evaluating Facilitator Training Effectiveness Using Kirkpatrick Model in Indonesian Legislative Institution - Sorayya, Hilalatus; Iqbal, Muhammad; Irawan, M. Ary (Transformasi : Jurnal Penelitian dan Pengembangan Pendidikan Non Formal Informal, 2025)
This study aims at evaluating the facilitator capacity building training program at the Legislative Human Resources Competency Development Center of the Indonesian House of Representatives Secretariat General, using the Level 1 and 2 Kirkpatrick evaluation model. This descriptive quantitative research employed total sampling technique with 28 participants from 12 different functional positions and work units. The evaluation was conducted using questionnaires based on Kirkpatrick's evaluation model, focusing on Level 1 (Reaction) and Level 2 (Learning). Data were analyzed using descriptive statistics with scores classified into five categories ranging from "Very Poor" to "Very Satisfactory". Level 1 evaluation showed excellent results across all indicators: lecturers scored 87.09, instructors averaged 90.48-94.64 across four training days, examiners achieved 95.12, and training organizers received 92.02. All scores fell within the "Very Satisfactory" category. Level 2 evaluation demonstrated successful learning outcomes, with all 28 participants achieving competent ratings in microteaching sessions (average score: 87.43, range: 79.7-92.4). The facilitator capacity building training program effectively met participants' expectations and learning objectives. The consistently high satisfaction scores and successful practical applications in microteaching indicate that the training successfully enhanced participants' facilitation competencies.